2001
DOI: 10.1073/pnas.171065898
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of termination of DNA replication of Escherichia coli involves helicase–contrahelicase interaction

Abstract: protein-protein interaction ͉ replication arrest ͉ two-hybrid analysis ͉ reverse two-hybrid analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(98 citation statements)
references
References 27 publications
8
89
0
Order By: Relevance
“…The 'mousetrap' model of Tus-Ter RF pausing posits that a specific interaction is required between Tus and a critical 'locking cytosine' residue within TerB that is revealed by DNA strand separation 22 . An alternative model proposes that RF arrest at Tus-Ter is mediated by specific protein-protein interactions in E. coli 23,24 . Our data suggest that, although additional proteins may be required to reinforce RF pausing at Tus-Ter in E. coli 23,24 , these are clearly not required for Tus-Ter to function as a polar RF barrier in yeast.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%
“…The 'mousetrap' model of Tus-Ter RF pausing posits that a specific interaction is required between Tus and a critical 'locking cytosine' residue within TerB that is revealed by DNA strand separation 22 . An alternative model proposes that RF arrest at Tus-Ter is mediated by specific protein-protein interactions in E. coli 23,24 . Our data suggest that, although additional proteins may be required to reinforce RF pausing at Tus-Ter in E. coli 23,24 , these are clearly not required for Tus-Ter to function as a polar RF barrier in yeast.…”
Section: Tus-ter Modules Cause Polar Rf Pausing In Yeast the 21-bpmentioning
confidence: 99%
“…We further observed that mutant E49K, which is hypothesized to be deficient in polar replication fork arrest due to the elimination of specific protein-protein interactions 13,14 , gave rise to lifetimes identical to that of wt Tus, only now with a severely decreased probability of entering the longest-lived state. This ties the observed deficiency of in vivo fork arrest to the drop in occurrence of the longest-lived state found in our experiments.…”
Section: Discussionmentioning
confidence: 72%
“…A more direct link between our probabilities and in vivo arrest efficiencies will require knowledge of, for example, the amount of work performed by a replisome. It remains to be determined to what extent the two shortest-lived lock states are capable of causing arrest of DNA-processing enzymes, though the reported replisome arrest deficiency of E49K 13,14 together with our observation that E49K affects only the longest-lived state, suggests that these intermediate states are not sufficient to block replication fork progression. It is clear though that these two 'lesser' lock states still pose a significant barrier to strand separation, much more so than the mere binding of Tus alone.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations